The Effect of Listening To Slow-Tempo Classical Music on Reading Comprehension in Students - Nadillah Aprilyani; Ahmad Arfandi; Ajeng Mutiara Anggita; Ratna Yunita Setiyani Subardjo (CV. Doki Course and Training, 2024)
Reading comprehension is a critical component of the learning process, particularly for students, as it is considered a fundamental skill that must be acquired. The current study utilizes the first movement of Beethoven's